Chinese consumers' willingness to pay for pork traceability information—the case of Wuxi. (January 2016) - Wu, Linhai; Wang, Hongsha; Zhu, Dian; Hu, Wuyang; Wang, Shuxian
Abstract: In this study, consumers' willingness to pay for farming, slaughter and processing, distribution and marketing, and government certification information was investigated in Wuxi, Jiangsu Province, China using an experimental auction and real choice experiment based on incentive compatibility of the nonhypothetical elicitation method. No significant differences in consumers' willingness to pay were revealed by the experimental auction and real choice experiment on the whole, and results from both nonhypothetical experimental methods demonstrated that consumers were willing to pay certain premiums for all four types of traceability information and had the highest willingness to pay for government certification information. These results indicate that consumers trust in pork safety protection under governmental supervision. Moreover, it was found that government certification information played a significant role in improving consumer utility, demonstrating that consumers paid close attention to safety risks in farming. Therefore, this study predicts that the introduction of governmental supervision into the pork traceability system and establishment of a system for collecting traceability information starting from the stage of pig farming will play important roles in meeting consumer demands for pork quality and safety, as well as promoting the development of traceable food policies.